Efficacy of R-COMP in comparison to R-CHOP in patients with DLBCL: A systematic review and single-arm metanalysis. (July 2021) - Visco, Carlo; Pregnolato, Francesca; Ferrarini, Isacco; De Marco, Beatrice; Bonuomo, Valentina; Sbisà, Eugenio; Fraenza, Costanza; Bernardelli, Andrea; Tanasi, Ilaria; Quaglia, Francesca Maria; Krampera, Mauro
Graphical abstract: Highlights: Standard of care for aggressive lymphoma is poorly tolerated in the aged population. Non-pegylated liposomal doxorubicin (NPLD) is less cardiotoxic. Its efficacy in comparison with conventional doxorubicin is still a matter of debate. Our metanalysis endorses the value of NPLD both in terms of response and survival. NPLD may allow more patients to access the ideal cure for their disease. Abstract: Doxorubicin represents the mainstay in the upfront treatment of diffuse large B-cell lymphoma (DLBCL) patients. However, its administration is sometimes hampered by the coexistence of former comorbidities/cardiac issues, especially in the elderly population. Liposome encapsulated drug delivery systems have been adopted to reduce the exposure of normal tissues to the drug, both in solid cancers and lymphomas. Despite claims for lower toxicity, the efficacy of non-pegylated liposome doxorubicin (NPLD) in DLBCL, as compared to standard doxorubicin, has never been established. We systematically reviewed relevant literature of NPLD in lymphoma treatment. Adjusting for age/comorbidities, our metanalysis revealed that the use of combinations including NPLD (R-COMP) were non-inferior in terms of response, overall and progression-free survival to the standard of care (R-CHOP) in overlapping series of DLBCL patients. R-COMP may represent a safe and active option for elderly patients with DLBCL, or for those with some extent of cardiac impairment at baseline.